Association of plasma interleukin-6 with infarct size, reperfusion injury, and adverse remodelling after ST-elevation myocardial infarction. Issue 2 (25th November 2021) - Tiller, Christina; Reindl, Martin; Holzknecht, Magdalena; Lechner, Ivan; Schwaiger, Johannes; Brenner, Christoph; Mayr, Agnes; Klug, Gert; Bauer, Axel; Metzler, Bernhard; Reinstadler, Sebastian J
Abstract: Aims : Little is known about the clinical relevance of interleukin (IL)-6 in patients with acute ST-elevation myocardial infarction (STEMI). This study examined the possible associations of plasma IL-6 concentrations with infarct size (IS), reperfusion injury and adverse left ventricular remodelling (LVR), in STEMI patients treated with primary percutaneous coronary intervention (PCI). Methods and results: We prospectively included 170 consecutive STEMI patients (median age 57 years, 14% women) treated with primary PCI between 2017 and 2019. Blood samples for biomarker analyses including IL-6 were collected on Day 2. Left ventricular ejection fraction (LVEF), IS, and reperfusion injury [microvascular obstruction (MVO) and intramyocardial haemorrhage (IMH)] were determined using cardiac magnetic resonance (CMR) imaging on Day 4. Left ventricular remodelling was defined as ≥10% increase in left ventricular end-diastolic volume from baseline to 4 months CMR follow-up. Patients with IL-6 concentrations ≥median (17 ng/L) showed a significantly lower LVEF (43% vs. 52%, P < 0.001), larger IS (22% vs. 13%, P < 0.001), larger MVO (1.9% vs. 0.0%, P < 0.001), and more frequent IMH (52% vs. 18%, P < 0.001). Left ventricular remodelling was more common in patients with IL-6 ≥ median (24% vs. 9%, P = 0.005). In both linear and binary multivariable regression analyses, IL-6 remained independently associated with lower LVEF [odds ratio (OR): 0.10, 95% confidence interval (CI) 0.02–0.42, P = 0.002], larger IS (OR: 5.29, 95% CI 1.52–18.40, P = 0.009), larger MVO (OR: 5.20, 95% CI 1.30–20.85, P = 0.020), with presence of IMH (OR: 3.73, 95% CI 1.27–10.99, P = 0.017), and adverse LVR (OR: 2.72, 95% 1.06–6.98, P = 0.038). Conclusions : High concentrations of circulating plasma IL-6 on Day 2 after STEMI were independently associated with worse myocardial function, larger infarct extent, more severe reperfusion injury, and a higher likelihood for LVR, suggesting IL-6 as a useful biomarker of more serious outcome and potential therapeutic target. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT04113356;NCT04113356 . Graphical Abstract: